The propensity to patent in oligopolistic markets - Alexandra K. Zaby (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2009)
We analyze the strategic protection decision of an innovator between a patent and secrecy in a setting with horizontally differentiated products. By introducing the patenting decision into the well known circular city model, the impact of the disclosure requirement linked to a patent application as well as the problem of legally inventing around a patent can be taken into account. Asymmetry in the circular market leads to a consumer migration effect. We find that secrecy may be the innovator's profit maximizing strategy whenever the mandatory disclosure of information enhances the market entry of competitors.
urn:nbn:de:bsz:21-opus-42006
Keywords: L13; L24; O34; 330; patenting decision; secrecy; disclosure requirement; patent breadth; horizontal product differentiation; circular city; Innovation; Patent; Geheimhaltung; Lizenzvergabe; Produktdifferenzierung; Räumlicher Wettbewerb; Oligopol; Theorie